2023
DOI: 10.3390/languages8010023
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Duration of Pauses in Relation to Speech Tempo and Structural Organization in Two Speech Genres

Abstract: Pauses act as important acoustic cues to prosodic phrase boundaries. However, the distribution and phonetic characteristics of pauses have not yet been fully described either cross-linguistically or in different genres and speech styles within languages. The current study examines the pausal performance of 24 Czech speakers in two genres of read speech: news reading and poetry reciting. The pause rate and pause duration are related to genre differences, overt and covert text organization, and speech tempo. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…In acoustic studies of political speech and speakers, Duez already observed in 1982 that the more uninterrupted, monologue-like and pre-planned the speaking context is, the greater the duration of pauses [4]. Public speeches can therefore be expected to feature relatively long pauses, and news readings to have on average shorter pauses than poetry recitations, which is indeed in accord with recent evidence provided by [5]. Fifteen years later, Duez added to her findings that, with increasing authority and social standing, the pauses speakers make in their speeches become longer and more frequent [1].…”
Section: Introduction 1phonetic Characteristics Of Silent Pausessupporting
confidence: 70%
See 4 more Smart Citations
“…In acoustic studies of political speech and speakers, Duez already observed in 1982 that the more uninterrupted, monologue-like and pre-planned the speaking context is, the greater the duration of pauses [4]. Public speeches can therefore be expected to feature relatively long pauses, and news readings to have on average shorter pauses than poetry recitations, which is indeed in accord with recent evidence provided by [5]. Fifteen years later, Duez added to her findings that, with increasing authority and social standing, the pauses speakers make in their speeches become longer and more frequent [1].…”
Section: Introduction 1phonetic Characteristics Of Silent Pausessupporting
confidence: 70%
“…This difference in variation magnitude is also significant according to a supplementary F test (F[45,35]= 2.656, p=0.004). Furthermore, Obama's pause durations -even those of the MM pauses -are overall remarkably long, as is illustrated by the histogram in Figure 8, compared to a histogram we created after the data of silent pauses in other speaker's read speech performances from the study of Campione & Véronis [6]; see also the overview provided by Heldner & Edlund [58] and the study of Sturn & Volin [5], who report similar pause-duration distributions (and mean values for silent intervals of about 480-530 ms) both for news readings and poetry recitations. In all above mentioned previous studies, pauses > 2,000ms are "exotic" insofar as they represent less than 5% of the respective data sample.…”
Section: Pause Durationmentioning
confidence: 94%
See 3 more Smart Citations